2022
DOI: 10.3389/fpsyt.2022.791333
|View full text |Cite
|
Sign up to set email alerts
|

“Our Patients Are Different”: Predictors of Seclusion and Restraint in 31 Psychiatric Hospitals

Abstract: BackgroundResearch in recent years has demonstrated that the use of coercive measures such as seclusion and restraint differs very much between hospitals within a country. In 2015, a central register for all coercive measures in the German federal state of Baden-Wuerttemberg has been established for 32 hospitals treating involuntary patients. The objective of the present study was to identify factors that determine the differences between these hospitals.MethodsData on coercive measures and diagnoses from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
7
0
3
Order By: Relevance
“…Another limitation is the very likely presence of unknown confounders. In a previous study on differences between hospitals in the rates of coercive measures, only 27% of the variation could be explained by a wide range of structural data of hospitals and supply areas [ 24 ]. With respect to data quality, no findings are available on the reliability of the data collected.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is the very likely presence of unknown confounders. In a previous study on differences between hospitals in the rates of coercive measures, only 27% of the variation could be explained by a wide range of structural data of hospitals and supply areas [ 24 ]. With respect to data quality, no findings are available on the reliability of the data collected.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation of fewer IPAs during lockdowns in our study could be the reduction in psychiatric hospital beds during the COVID-19 pandemic, 23 as the association of available beds and the number of IPAs has been well described in the literature. 13 It also seems important to mention the effects of the COVID-19 prevention strategies on the open-door policy of many psychiatric hospitals in Austria, 29 as a corresponding open-door policy could no longer be maintained, at least temporarily. Open-door policies tend to be associated with lower accommodation rates, at least in Austria.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] Although numerous factors have been identified that influence the use of coercive measures, such as the number of hospital beds per region, medical resources including the patient-staff ratio, staff training and attitudes, and architecture, many questions remain unanswered. 7,8,[10][11][12][13] These include how a pandemic and preventive restrictions such as lockdowns affect not only general mental healthcare but also the use of coercive measures. The global outbreak of the COVID-19 pandemic in early 2020, which led to one of the greatest global social, economic and healthcare challenges in recent decades and has jeopardised the regular support and care of people with mental health conditions, has made it possible to pursue this question.…”
mentioning
confidence: 99%
“…Vermeintlich "fairere" Vergleiche mittels statistischer Adjustierungsverfahren werfen damit zahlreiche neue Probleme der Interpretation auf und erhöhen die Transparenz nicht unbedingt [9]. Der einzige robuste Prädiktor für die Häufigkeit von Zwangsmaßnahmen in psychiatrischen Kliniken, der konsistent bestätigt werden konnte, ist -wenig überraschend -der Anteil unfreiwillig aufgenommener Patienten [9,10]. Strukturmerkmale der Kliniken und der Versorgungsregionen erklären allerdings so wenig Varianz, dass doch auch von wirksamen Unterschieden der klinischen Praxis ausgegangen werden muss, die sich in "weichen" Faktoren wie Einstellungen, tradierten Verfahrensweisen, internen Abläufen usw.…”
Section: Fragestellungen Und Ergebnisseunclassified
“…Strukturmerkmale der Kliniken und der Versorgungsregionen erklären allerdings so wenig Varianz, dass doch auch von wirksamen Unterschieden der klinischen Praxis ausgegangen werden muss, die sich in "weichen" Faktoren wie Einstellungen, tradierten Verfahrensweisen, internen Abläufen usw. wiederfinden und Ansatzpunkte für Veränderungen bieten [9,10].…”
Section: Fragestellungen Und Ergebnisseunclassified